2009
DOI: 10.1158/1078-0432.ccr-09-2131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of VHL Gene Alterations and their Relationship to Clinical Parameters in Sporadic Conventional Renal Cell Carcinoma

Abstract: Purpose: This study aimed to carry out a comprehensive analysis of genetic and epigenetic changes of the von Hippel Lindau (VHL) gene in patients with conventional (clear cell) renal cell carcinoma and to determine their significance relative to clinicopathologic characteristics and outcome. Experimental Design: The VHL status in 86 conventional renal cell carcinomas was determined by mutation detection, loss of heterozygosity (LOH), and promoter methylation analysis, extending our original cohort to a total o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 45 publications
10
125
1
2
Order By: Relevance
“…Only 3% of the cases showed wild type VHL. 30 In this study we performed FISH analysis for 3p deletion on samples from multilocular cystic renal cell carcinomas and compared the findings with those from a population of similarly low grade conventional clear cell renal cell carcinomas. Deletion in 3p was observed in 74% of the multilocular cystic renal cell carcinomas and in 89% of the clear cell renal cell carcinomas with no statistically significant difference in the incidence of 3p deletion, between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3% of the cases showed wild type VHL. 30 In this study we performed FISH analysis for 3p deletion on samples from multilocular cystic renal cell carcinomas and compared the findings with those from a population of similarly low grade conventional clear cell renal cell carcinomas. Deletion in 3p was observed in 74% of the multilocular cystic renal cell carcinomas and in 89% of the clear cell renal cell carcinomas with no statistically significant difference in the incidence of 3p deletion, between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…3a), and unregulated β-catenin activation increases the tumourgenicity of renal cells 74 . In addition, VHL is inactivated in ~11-30% of ccRCC and pRCC by promoter methylation [75][76][77] or by loss of chromosome 3. In the absence of pVHL, β-catenin can be targeted for degradation by the E3 ligase F-box/WD repeat-containing protein 1A (β-TrCP, also called β-transducin repeat containing protein) 72,73,78 .…”
Section: Frequently Dysregulated Pathways Wnt-β-catenin Met and Slitmentioning
confidence: 99%
“…von Hippel-Lindau (VHL) disease is caused by inactivating germline mutations of the VHL tumor-suppressor gene and is associated with an increased risk of ccRCC and other tumors, including pheochromocytoma, and hemangioblastoma of the retina, cerebellum and spinal cord (Woodward and Maher, 2006). In addition, it has been reported that biallelic inactivation of the VHL gene also occurs in the majority of sporadic ccRCCs (Young et al, 2009). These observations have motivated studies aimed at determining how the VHL protein (pVHL) suppresses tumor growth.…”
Section: Introductionmentioning
confidence: 99%